Determination of Poly(ethylene glycol)-Binding to Browse Foliage, as an Assay of Tannin, by Near-Infrared Reflectance Spectroscopy - Landau, Serge; Dvash, Levana; Decandia, Mauro; Cabiddu, Andrea; Shapiro, Fira; Molle, Giovanni; Silanikove, Nissim (Journal of Agricultural and Food Chemistry, 2004)
Nutritionists are interested in functional assays of tannins that do not require time-consuming and expensive extraction, such as the 14C-labeled poly(ethylene glycol) (PEG)-binding (PEG-b) assay. This paper reports the application of near-infrared (NIR) spectroscopy to determine the percentage of PEG binding, in place of the 14C-labeled PEG-b assay of tannin, in Mediterranean woodland vegetation. Calibration was done with 53 samples from 14 species and was validated on 25 samples from 10 species. PEG-b ranged between 1.4 and 20.7% in the samples. The calibration obtained by using the modified partial least-squares (MPLS) method, with all wavelengths in the 1100?2500 nm range combined, and the validation were reasonably linear (R?2 = 0.96 and 0.91, respectively). The accuracies, estimated from the standard errors of cross-validation and prediction, were ±1.6 and ±1.7% PEG-b, respectively. The NIRS-aided procedure proposed here can serve as an accurate, inexpensive, time-saving, and environment-friendly functional assay of tannin in Mediterranean browse. Keywords: NIRS; goats; nutrition; poly(ethylene glycol); pasture
From Duplicate 1 (Determination of Poly(ethylene glycol)-Binding to Browse Foliage, as an Assay of Tannin, by Near-Infrared Reflectance Spectroscopy - Landau, Serge; Dvash, Levana; Decandia, Mauro; Cabiddu, Andrea; Shapiro, Fira; Molle, Giovanni; Silanikove, Nissim)
Keywords: Animal Nutritional Physiological Phenomena; Animals; Carbon Radioisotopes; Fabaceae; Fabaceae: chemistry; Goats; Hydrolyzable Tannins; Hydrolyzable Tannins: analysis; Near-Infrared; NIRS; nutrition; pasture; poly(ethylene glycol); Polyethylene Glycols; Polyethylene Glycols: metabolism; Spectroscopy